Pengaruh Manajemen terhadap Mutu Pendidikan Sekolah - Yusi Srihartini (As-Syar'i: Jurnal Bimbingan & Konseling Keluarga, 2019)
This research was conducted with the aim of seeking information that there was an influence of management on improving the quality of school education, based on the Education Unit Level Curriculum or abbreviated as the KTSP in 2006. The study was conducted on elementary level education staff (SD / MI and SMP / MTS) and intermediate (SMA / MA and SMK / MAK) who have implemented the curriculum, especially the Jakarta area. The results of the study for the group of education workers who implemented KTSP management had an average of 6.97 and for the group of educators who did not implement the KTSP obtained Lₒ of 0.1204 and for the group of educators not implementing KTSP management it was obtained at 0.1268 while L table for 40educators, a significant level of 0.05 at 0.14 means lₒ <Ltabel. It can be concluded that the population has a normal distribution. The results of the homogeneity research obtained X counts of 0.0053 X² table of 3.84 means that X² counts <x² tables, it can be concluded that both populations have the same variance or homogeneity. Testing the hypothesis by using the t test obtained t count of 2.1483 while the significant level of 0.05 degrees of freedom 78 obtained t table of 1.66 means t count> t table then Hᵃ is accepted so that there is management influence on the quality of school education for educational units implementthe KTSP.